Chagas diseases - Amaral, Isadora Max; Machado, Ana Eliza; Nascimento, Lígia Braz Benfica do; Oliveira, Sarah dos Santos; Alvarenga, Janaina Sousa Campos; Alvarenga, Ângela Cardoso (Seven Editora, 2024)
Introduction: Chagas disease, also known as American trypanosomiasis, is a slowly progressing chronic condition that mainly affects the heart muscle and the smooth muscle of the digestive tract. The World Health Organization recognized the disease in 2005 as a neglected tropical disease, which contributed to raising international awareness. Aim: To provide a more comprehensive overview of Chagas disease, exploring specific characteristics in order to combat misinformation about this public health condition. Etiological agent:  Trypanosoma cruzi is a protozoan of the Trypanosomatidae family, unicellular, with an elongated "C" shaped cell and a single flagellum at the anterior end. Vector: The vectors of Chagas' disease are triatomine insects - which are nocturnal and have a life expectancy of 1 to 2 years - also known as barbers. The most epidemiologically relevant genera are Panstrongylus, Triatoma and Rhodnius. Evolutionary forms: The different forms ( trypomastigote, epimastigote and amastigote) of Trypanosoma cruzi play specific roles in the parasite's life cycle, involving transmission, reproduction and infection in hosts. Forms of contamination: Cont amination in Chagas disease can be via the vector, through the feces that are eliminated at the time of the bite, vertical transmission, oral transmission, blood transfusion, organ transplantation and transmission through laboratory accidents. Biological cycle: The parasite's life cycle is complex and involves invertebrate hosts (barbers) and different species of wild and domestic mammals, including man. Clinical manifestations: This is a chronic disease. In the initial, acute phase, most patients are asymptomatic and then progress to the indeterminate form of the disease, which can last for decades. Years later, the patient may present in chronic stages, the cardiac form; with cardiopathy associated with myocarditis and fibrosis that results in heart failure, blood clot formation and cerebrovascular accidents; or the digestive form with alterations such as megacolon and/or megaesophagus, which may be associated with gastrointestinal disorders, Diagnosis: The diagnosis, in the acute phase is made from the direct parasitological examination on a blood slide. In the chronic phase, the disease is rarely detected, as most individuals are asymptomatic Treatment: Treatment consists of the use of drugs such as Benznidazole and Nifurtimox. Prophylaxis: With regard to the prevention of Chagas disease, vector control measures such as the application of long-lasting insecticides in homes and peridomiciliary structures are essential. In addition, improving the quality of domestic structures, serological screening of blood components, mosquito screens on doors and windows are also measures used.  Conclusion: Chagas disease represents a significant public health challenge due to the chronic cases of the disease, which are complex and manifest themselves in different ways. It is essential to emphasize the importance of updating information and consulting health professionals in order to properly manage this condition. DOI:https://doi.org/10.56238/sevened2024.007-052